ATF6β is not essential for the development of physiological cardiac hypertrophy - Emery Davis; Mohammad-Reza Shokri; Mary B. Rowland; Thomas York; Caroline T. Cohen; Anna Grace Johnson; Patrick E. Moore; Saige Schweitzer; Jon Sin; Chuong Bui; Robert N. Correll (PLoS ONE, 2025)
Physiological cardiac hypertrophy is a compensatory remodeling of the heart in response to stimuli such as exercise training or pregnancy that is reversible and well-tolerated. We previously described how the activating transcription factor 6 (ATF6) proteins, ATF6α and ATF6β, were required for pathological hypertrophy in response to hemodynamic stress. Here, we examine the functional roles of both ATF6 proteins in the context of exercise-induced physiological hypertrophy. After 20 days of swim training, we found differential roles: whole body gene-deleted mice lacking ATF6α had an attenuated hypertrophic response compared to wild-type mice but those lacking ATF6β did not. Additionally, mice lacking ATF6α displayed ventricular dilation and reduced fractional shortening after swimming. While we observed no differences in the expression of downstream UPR signaling between the exercise groups, mice lacking ATF6α showed enhanced phosphorylation of extracellular signal-regulated kinase 1/2 (ERK1/2). Thus, in response to swim training, loss of ATF6β did not hinder the development of physiological hypertrophy, but loss of ATF6α resulted in significantly reduced cardiac fractional shortening.